(untitled) (Bangladesh Journal of Microbiology, 2016)
In the present study fifteen Lactic Acid Bacteria (LAB) from milk and milk products were isolated, identified and tested for their antagonistic activity. All the samples were found to be acidic with a pH range of 6.0 to 6.8.The collected samples showed higher number of total bacterial load ranging from 3.24´10 5 to 1.04´10 8 cfu/ml. Out of fifteen isolates, nine isolates were found to belong to the genus Lactobacillus and identified as L. casei subsp. pseudoplantarum, L. homohiochii, L. salivarius, L. xylosus, L.fermentum, L.leichmannii , L.heterohiochii, L.casei, and L.plantarum,.The others were found to belong to the genus Streptococcus and identified as S. thermophilus , S. lactis, S. uberis, S.suis, S. faecalis, and S. equnius.The isolates showed antibacterial activity against four gram positive bacteria (Bacillus cereus, B. subtilis, B.megaterium, Staphylococcus aureus) and six gram negative bacteria (Escherichia coli, Shigella dysenteriae, Salmonella typhi, Salmonella paratyphi, Vibrio cholerae and Pseudomonas aeruginosa) by using the disc diffusion method. They also showed their antifungal activity against two fungi (Penicillium sp. and Aspergillus flavus) by modifying poisoned food technique. All of the fifteen isolates were active against one or more test pathogenic bacterial strains. Among them L. homohiochii (TM3/a) showed the highest zone of inhibition (30.3mm) against Salmonella typhi. Lactobacillus spp. showed more antifungal activity than Streptococcus spp. and Streptococcus uberis (TY4 /a) showed the highest antifungal activity (50%) against Penicillium sp.This preliminary work shows the potential application of LAB to improve safety of traditional fermented food and milk products. Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 76-82